PAIN MANAGEMENT: EFFECT OF CHEWING EXERCISES IN POST TONSILLECTOMY PATIENTS - Nawal Khurshid,; Altaf Hussain,; Khurshied, Saleh (Journal of Postgraduate Medical Institute, 2023)
Objective: To assess the effect of chewing in addition to pharmacological management of post-tonsillectomy pain and return to the normal diet. Methodology: To determine the impact of chewing gum on post-operative pain, a 12-month comparative cross-sectional study was carried out on 87 post-tonsillectomy patients at the Pakistan Institute of Medical Sciences (PIMS) Islamabad. Two groups of patients having elective tonsillectomy were created: Group A (chewing gum) and Group B. (routine care). Following surgery, patients were monitored to assess postoperative pain using a Visual Analogue Scale (VAS) from day 1 to day 7 and resume their regular diet. Results: Out of 87 patients, 49 (56.3%) belonged to group A, and 38 (43.7%) belonged to group B. Mean age of the participants was 23.8±5.2 years. The total number of male and female participants was 56 (64.4%) and 31 (35.6%) respectively. There was significantly lesser pain experienced by patients in group A as compared to group B from day 2 through day 5 (p<0.001), whereas there were no statistically significant differences observed between the two groups on the 1st,6th and 7th post-operative days in terms of post-op pain (p=0.589, 0.516, 0.376). In terms of resuming a normal diet, there was no statistically significant difference between the two groups. (p= 0.456). Conclusion: Postoperative use of chewing exercises significantly decreases pain in the immediate post-tonsillectomy period and is recommended for use as a non-pharmacological adjunct for post-tonsillectomy pain management.